PERILAKU KONSUMTIF DITINJAU DARI KONTROL DIRI PADA REMAJA DI SMU WR.SUPRATMAN I MEDAN - Suviona suviona (unprimdn.ac.id, 2020)
This study aims to determine the relationship between consumer behavior and self-control. The hypothesis of this study states that there is a negative relationship between self-control with the consumer behavior, with an assumption the higher self-control, the lower the consumer behavior and conversely the lower the self-control, the higher the consumer behavior. Subjects of the study were students of SMU WR.Supratman I Medan consisting of 100 students who were selected by purposive sampling method. Data were obtained from a scale to measure self-control and consumer behavior. The calculation was performed by means of testing requirements analysis (assumption) that consists of a test for normality and linearity test relationships. Analysis of the data used is Product Moment Correlation with SPSS 17 for Windows. The results of data analysis showed that a correlation coefficient was -0.554 with p 0.000 (p <0.05). This shows there is a negative relationship between self-control and the consumer behavior. These results indicate that the contribution given to the control variable on consumer behavior was 30.7 percent and the remaining 69.3 percent was affected by other factors such as motivation, personality and self-esteem. From these results, it can be concluded that the hypothesis stating that there is a negative relationship between self-control and consumer behavior, is acceptable.